Gamma-Ray Technology in Secondary Metabolite Production for Sustainable Agriculture: Article Review - Arifin, Zainal; Ardo, Tanjung (Agrifarm : Jurnal Ilmu Pertanian, 2025)
The increasing worldwide demand for natural products in fields ranging from pharmaceuticals to food industry has made clear an urgent necessity of more effective and sustainable production technologies. In this regard, the gamma-ray technology is a very promising Biotechnological tool of choice. Because of its effective physical mutation and unique biological effects, gamma irradiation has been responsible for more than 60% of professionally released mutant crop verities. This approach possesses the potential to exploit the mutagenic effects of ionizing radiation, and to cause genetic diversity in plants for their agronomic traits such as yield productivity and specifically at large scale, the enhancement of important secondary metabolite profiles. The utility of gamma rays goes beyond mutations induction: as an elicitor, they cause dramatic physiological and molecular responses in plants leading to the overproduction of bioactive compounds. The mode of action may be through the generation of DNA damage, e.g., single and double strand breaks, which runs a novel pathway or activates an alternative one leading to enhanced production of certain secondary metabolites. This review intended to comprehensively discuss the versatile bioprocesses of gamma irradiation, biological mechanisms underlying its action and how this effect interprets into metabolite production, crop quality and overall agricultural sustainability. The application of this technology provides a promising option not only to improve the productivity high-value natural products but also the development of new plant germplasms with enhanced resilience (or stress tolerance) that is relevant for securing food production in an era of climate change.